Analysis of tax administration of large taxpayers in Uzbekistan for 2024 - Muzaffarov Dilshod Shukhratovich (Genius Journals, 2025)
This article analyzes the foreign experience of implementing the tax administration of large taxpayers, as a result of this analysis, issues of improving the tax legislation of the Republic of Uzbekistan, a proposal for further improvement of the tax administration of large taxpayers and recommendations are developed
Keywords: tax; budget policy; budget; tax rate